Chen Wen Hsi: more than Chinese painting - Lee, Ju-Lyn (Nanyang Technological University, 2022)
This thesis begins with an exploration on the roles or place of exhibitions and exhibitionary activities in a painter’s artistic practice based in Singapore in the twentieth century, specifically Chen Wen Hsi, a master of Chinese ink painting and one of the most important pioneers of Singapore art. Chen is also representative of “Nanyang art” and overseas Chinese artists. The research aims to learn the scope of Chen’s participation in exhibitions and exhibitionary activities, and if and how these might complement his artistic practice. It focuses on Chen’s intentions and begins by chronologizing his involvements with exhibitions and exhibitionary activities documented in newspaper archives, and analysing three categories of his participations. First some observations across the exhibitions at which he exhibited paintings are presented. These are followed by findings on his other involvements in exhibitionary activities, such as being part of selection panels for exhibitions, with focus on a 1976 exhibition he “organised” and “hosted”, and the two galleries he owned. Finally, his showcasing of acts of painting, such as at huihao sessions, painting demonstrations, and collaborative or joint paintings sessions, are discussed and related to their being featured in photographs and the newspapers. Besides the newpapers materials, the research is supplemented by extended literature, including the transcript of a 1983 interview of Chen, as well as an interview with Wee Beng Chong, co-participant of several of these activities. The findings illustrate that for Chen, exhibitions, exhibitionary activities, and its related structures are means of accessing financial support, navigating art infrastructure, and research. More importantly, they demonstrate that he also activated them as medium or form to transfer his artistic ideologies, such as on the combinations of the “East” and “West”, traditionality and modernity, and the importance of individualism, innovation, and internationalisation. Thus, this thesis proposes that Chen’s artistic practice comprise more than just painting.